2006
DOI: 10.1007/s10620-006-8029-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Colectomy on Immediate–Early Proto-Oncogene Expression and Hepatic Regeneration in the Rat

Abstract: The intact liver exists in a state of replicative quiescence. The factor(s) responsible for maintaining this state and their tissue sources have yet to be identified. Because the colon synthesizes and/or absorbs numerous agents that inhibit hepatocyte proliferation, the principle purpose of this study was to determine whether total colectomy would result in the conversion of quiescent livers to a state of replicative competence. Thus, adult, male Sprague-Dawley rats (250-300 g) were randomized to undergo eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In response to PH, JNK-c-Jun/AP-1, composed of the products of the Jun and fos families of genes, is rapidly induced [23,24] . We found that 0.2% CA diets could make c-Jun mRNA expression increase rapidly and maintain a comparatively high level for a longer time, similar to the results described by Kren [20] .…”
Section: Discussionmentioning
confidence: 99%
“…In response to PH, JNK-c-Jun/AP-1, composed of the products of the Jun and fos families of genes, is rapidly induced [23,24] . We found that 0.2% CA diets could make c-Jun mRNA expression increase rapidly and maintain a comparatively high level for a longer time, similar to the results described by Kren [20] .…”
Section: Discussionmentioning
confidence: 99%